Membangun Kesadaran Lingkungan Melalui Pembelajaran IPS Pada Siswa Kelas 4 Sekolah Dasar - Lusiana, Rosalia Eka (CV. Supernova Office Stationary and Printing, 2024)
This study aims to identify effective learning methods in building environmental awareness in grade 4 elementary school students through Social Sciences (IPS) subjects. Given the importance of environmental awareness from an early age, basic education is a crucial phase in instilling values and attitudes of caring for the environment. Social studies, as a subject that covers social, economic, and environmental aspects, has great potential in shaping students' character and environmental insights. This study uses a qualitative approach with a descriptive method. Data were collected through observations, interviews, and in-depth literature studies. The results of the study show that social studies learning that integrates environmental issues can increase students' understanding and awareness of the importance of protecting the environment. Some strategies that have proven effective include the use of interactive learning media, group discussion methods, and environment-based projects. This learning not only improves students' factual knowledge, but also forms a sustainable mindset and behavior in maintaining the ecosystem. This study concludes that the integration of environmental materials in social studies learning is an effective approach to build environmental awareness in grade 4 students, and recommends the development of a curriculum that emphasizes more on environmental issues as well as training for teachers in using innovative learning methods.